O papel da proposta temática e das habilidades cognitivas na construção do percurso argumentativo e na elaboração da proposta de intervenção em redações do Enem - Sbroggio, Fernanda Martin (2017)
This dissertation is linked to the Reading, Writing, and Portuguese Language Teaching line of research and focuses on the relation between thematic composition, mobilization of cognitive abilities to select, relate, organize, and interpret, and the construction of argumentative route and of the proposals of intervention in ten argumentative essays elaborated for the writing test of Enem 2013. Based on theoretical lines linked to cognitive, interactionist, and rhetorical argumentative sciences, this research aims at verifying, with the analysis of these essays, the role of the thematic proposal, as well of the cognitive abilities in the construction of argumentative route and in the elaboration of the proposal of intervention in Enem writing test. For this purpose, the analysis of the writing test’s thematic composition is performed, as well as the verification of how the abilities to select, relate, organize, and interpret facts and opinions are mobilized in the development of arguments, the identification of the argumentative route built by the student, and the identification and evaluation of the proposals of intervention presented. At the end of this route, it is possible to observe that both the thematic proposal and the mobilization of cognitive abilities interfere with the meeting of competencies III and V, which refer to construction of argumentative route and elaboration of the proposal of intervention, respectively. If, on the one hand, the composition of the thematic proposal interferes more directly with the meeting of competency V, on the other hand, the development of cognitive abilities is crucial to the construction of a consistent, persuasive argument, which dialogs with the proposal of intervention. This finding supports the conclusion that extra caution is necessary in the elaboration of the thematic sentence, in order to ensure that it dialogs completely with the reference matrix, instead of being a complicating factor to the meeting of the competencies analyzed in this study, as well as greater attention to these students’ basic education, which must intensify the exercise and development of thinking, in order to create citizens who are capable of mobilizing the most diverse cognitive abilities in order to accomplish a specific purpose. Given the importance of Enem in the national scenario, it is believed that the conclusions obtained by this research may be useful to expand understanding about the written test in the exam, as well as to offer a diagnosis of how understanding about the essay and the cognitive abilities necessary for its composition remain developed in the students who have already completed or are about to complete high school. This research may, as well, serve as basis to new and more detailed studies in this field